ANALISIS STRATEGI PEMBELAJARAN GURU DALAM MENUNJANG PRESTASI AKADEMIK TAMAN KANAK-KANAK NEGERI MARIO TAKKALALLA KECAMATAN MARIORIWAWO KABUPATEN SOPPENG - Damayanti; Aminah, Sitti; Syamsiar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Teacher Learning Strategy in Supporting Academic Achievement of Students of Mario Takalalla State Kindergarten is a teacher's effort to achieve academic achievement and abilities of early childhood students, especially students of Mario Takalalla State Kindergarten which includes cognitive aspects, affective aspects and psychomotor aspects. This study aims to analyze, review and describe teacher learning planning strategies in supporting early childhood academic achievement. This research method uses a descriptive method with a qualitative approach. Data collection techniques by means of observation, interviews and documentation. The research subjects are school supervisors, principals, class teachers and school committees. The results of the study show: 1) the learning strategy used by class teachers at Mario Takalalla State Kindergarten is a direct learning strategy by considering the characteristics of students by using active and joyful learning methods. This strategy can support students' academic achievement well from early childhood academic achievement indicators, namely cognitive, affective and psychomotor aspects. 2) Supporting factors such as individual teacher abilities, student motivation and the participation of students' parents greatly influence students' achievements from all aspects.